2019
DOI: 10.1115/1.4043073
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Propagation of Bending Waves in Wrinkled Films

Abstract: Wrinkling is a common phenomenon in natural and engineering film structures. The wrinkles influence the geometry and dynamic response of these structures. In this work, we investigate the wrinkling of a stretched thin film containing engineered microstructures and its derived functionality on controlling the propagation of bending waves. The underlying mechanism is revealed and the effect of wrinkles on the bandgap of bending waves is systematically evaluated via numerical simulations based on the Bloch wave t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Early designs use static and passive structures and have properties that cannot be changed after the metamaterials are fabricated (3,(14)(15)(16)(17). To address this issue, mechanical loads are used to change the metamaterial properties by altering the geometry through buckling or snapping (18)(19)(20). At the same time, the recent surge in the interests in smart structures that can dynamically change properties on demand has led to the emergence of active metamaterials (or stimuli-responsive metamaterials), which can transform into predetermined shapes when triggered by certain stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Early designs use static and passive structures and have properties that cannot be changed after the metamaterials are fabricated (3,(14)(15)(16)(17). To address this issue, mechanical loads are used to change the metamaterial properties by altering the geometry through buckling or snapping (18)(19)(20). At the same time, the recent surge in the interests in smart structures that can dynamically change properties on demand has led to the emergence of active metamaterials (or stimuli-responsive metamaterials), which can transform into predetermined shapes when triggered by certain stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…They fabricated wrinkled metal films on polydimethylsiloxane (PDMS) substrates using mismatch of thermal expansion, which introduced compression strain in the film and led to the formation of wrinkling. Both experimental and theoretical studies have shown that stiff thin film-soft substrate bilayer system and compression strain beyond a critical value in the film are required to form thin film wrinkling [3,11,[15][16][17][18][19][20][21][22][23][24][25]. It is a process to balance the bending energy of the thin film and the strain energy of the substrate by adopting specific wrinkling wavelength and amplitude [17,23,26,27].…”
Section: Introductionmentioning
confidence: 99%